A detailed performance analysis of a novel UWB flexible monopole antenna realized with airbrush technique for different technologies. (1st June 2022) - Geyikoglu, Mirac Dilruba; Cavusoglu, Bulent
Abstract: In this article, a detailed performance analysis of a novel flexible monopole antenna with a 141.46% impedance bandwidth in the 2.4–14 GHz ultrawideband (UWB) range is present. The antenna is fabricated on a flexible Kapton substrate with compact geometry for different technology applications under different bending conditions. The airbrush printed technique was preferred due to its advantages such as easy production, conductivity control, and no loss of surface waves. The antenna has dimensions of 82 × 57 × 0.125 mm 3 and is fed by a coplanar waveguide transmission line. All necessary antenna simulations are performed using Computer Simulation Technology (CST). According to the positions of identical antennas face to face, face to side, side to side, time-domain analysis is performed for the impact response analysis. The transmission coefficient characteristics ( S 21 ) and the group delay are measured for various bending conditions. Time and frequency domain analyzes show that the proposed UWB antenna has the much-needed stable performance in UWB antenna. The proposed UWB antenna has good performance over the operating spectrum for a flat and bending configuration.